Technological and Verification Training in the Spanish Media: El caso de los directores y jefes de sección - López-Martín, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Through a survey, this paper explores the level of education and training in data verification of editors and section chiefs of Spanish media (n=190). The results show a low level of training in this area, channelled mainly through courses given in their companies or self-taught learning. This leads to a meagre knowledge and use of specific digital tools to contrast information. This does not prevent them from having a generous self-perception about their skills in verification, although (almost) all respondents show a desire to participate in training activities.